Density, ultrasound speed and dynamic modulus of solid and laminated wood of Pinus pseudostrobus - Macedo Alquicira, Isarael; Sotomayor Castellanos, Javier Ramón (Instituto de Ecología, A.C., 2021)
Laminated wood can potentially replace solid wood to make a less variable and more homogeneous engineered material. There is little information that compares, simultaneously and in the same species, the ultrasound speeds, and the dynamic modules in solid versus laminated wood. The objective of the investigation was to verify experimentally, in small specimens, if the characteristics of Pinus pseudostrobus laminated wood are like those of solid wood. For this, their densities were calculated, and ultrasound tests were performed in the radial, tangential and longitudinal directions. Also, the speeds and dynamic modules were determined. The results indicate that the density of laminated wood increases, compared to that of solid wood. Speeds and dynamic moduli decrease in radial and tangential directions; instead, they increase for the longitudinal direction. It was experimentally verified that the magnitudes of density, velocity and dynamic modulus in laminated wood are like those of solid wood of this species. The variability in the studied characteristics decreases as an effect of reconstituting solid wood. For the speeds and dynamic modules of solid wood, their anisotropy ratios show proportions similar to those reported in the literature, but the magnitudes are specific to each species. The research provides reference data and shows that the solid and laminated wood of P. pseudostrobus can be characterized with a non-destructive method.